The role of transformational leadership, leader member exchange, digital transformation on organizational citizenship behaviour and work innovation capabilities in during Covid-19 pandemic - Calen Calen; Sri Aprianti Tarigan; Rosita Rosita; Susanto Susanto; Erina Alimin (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
The purpose of this study is to analyze the relationship between Transformational Leadership, Leader Member Exchange, Digital Transformation on Work Innovation Capabilities and Organizational Citizenship Behavior. In this study using quantitative methods and data analysis techniques Structural Equation Modeling (SEM) using SmartPLS 3.0 software. This research was conducted the sample units were 390 Micro, Small & Medium Enterprises (MSMEs). Based on the results of data analysis, it is concluded that transformational leadership has a significant effect on Work Innovation Capabilities, transformational leadership has no significant effect on Organizational Citizenship Behavior, Leader Member Exchange has a significant effect on Work Innovation Capabilities, Leader Member Exchange has no significant effect on Organizational Citizenship Behavior, digital transformation has no significant effect on Work Innovation Capabilities, digital Transformation has no significant effect on Organizational Citizenship Behavior, Work Innovation Capabilities have no significant effect on Organizational Citizenship Behavior, transformational Leadership has no significant effect on Work Innovation Capabilities through Organizational Citizenship Behavior, Leader Member Exchange has no significant effect on Work Innovation Capabilities via Organizational Citizens hip Behavior , digital transformation has no significant effect on Work Innovation Capabilities through Organizational Citizenship Behavior.